LOS RECURSOS DIDÁCTICOS Y EL APRENDIZAJE DE ECUACIONES DE PRIMER GRADO, EN LOS ESTUDIANTES DE DÉCIMO AÑO DE EDUCACIÓN GENERAL BÁSICA PARALELO “B” DE LA UNIDAD EDUCATIVA “PEDRO VICENTE MALDONADO”, EN EL PERÍODO SEPTIEMBRE 2019 – FEBRERO 2020 - Acan Inga, Jhoanna Araceli (2020)
At present, education is the only way to produce a change in society, so it is necessary that the use of teaching resources in the teaching process of Mathematics, because these materials play a very important role and promote an active, dynamic teaching in student, favoring the construction of content and developing in them competences, abilities, skills and creative thinking in order to motivate them to be interested in the subject. The research was conducted with the 31 students of Tenth Year of General Basic Education parallel "B" and 14 teachers of the Mathematics Area of the Educational Unit "Pedro Vicente Maldonado" whose objective was to determine the type of teaching resource that the educator uses in the linear equations learning process, to know this objective the different existing resources were conceptualized by means of documents, books, articles, bibliographic sources and later a survey was applied to both the student and the teacher to collect data that helped to specifically determine the educational material that the teacher uses in the classroom. The type of research was descriptive, field and bibliographic. Through this research it has been concluded that in the study of the first degree equations materials such as the blackboard, the study book, the educational software, projector are used, however there are other means with low percentage of use such as the didactic guide, interactive games, virtual classrooms, individual workshop, among others.